Optoelectronic heterodyne THz receiver for 100 - 300 GHz communication links - Deumer, Milan; Stiewe, Oliver; Nellen, Simon; Lauck, Sebastian; Breuer, Steffen; Kohlhaas, Robert B.; Schubert, Colja; Elschner, Robert; Freund, Ronald; Schell, Martin (IEEE access, 2024)
Terahertz wireless communications is an increasingly interesting research topic due to the high demand for un-allocated channels and high data rates. Photonic solutions have shown great potential in this field. However, most photonics assisted THz links so far have employed optoelectronics only on the transmit side. Thus, the full potential of photonic THz communication has not been utilized yet. Here, we introduce optoelectronics also on the receive side by using a photoconductive antenna based heterodyne THz detector. This allows down-conversion of data signals from the W-, D-, and THz-band to the baseband using a laser beat signal as local oscillator. Using electromagnetic modeling, we designed passive radio frequency structures and a receiver package to handle high intermediate frequency output signals. In a homodyne spectroscopic setup, the receiver shows a frequency response superior to state-of-the-art photoconductive antennas due to an improved photoconductive material. In a heterodyne testbed, the receiver exhibits a large intermediate frequency bandwidth of 11 GHz and a conversion gain of -47 dB. This enabled us to employ the receiver in a fully photonic wireless link at sub-terahertz and terahertz frequencies together with a PIN photodiode emitter. We achieved error-free transmission of 4-QAM signals with gross data rates up to 12 Gbit/s at carrier frequencies up to 320 GHz. This work shows the huge potential of optoelectronic receivers for THz wireless communications and enables the exploration of full photonic THz links.